2020
DOI: 10.2196/18633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Computer Debriefing on Acquisition and Retention of Learning After Screen-Based Simulation of Neonatal Resuscitation: Randomized Controlled Trial

Abstract: Background Debriefing is key in a simulation learning process. Objective This study focuses on the impact of computer debriefing on learning acquisition and retention after a screen-based simulation training on neonatal resuscitation designed for midwifery students. Methods Midwifery students participated in 2 screen-based simulation sessions, separated by 2 months, session 1 and session 2. They were randomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Additionally, 43% (n=23 of 54) of the included studies underwent post-assessment debriefing. Four studies using debriefing as a hypothesis supported its positive effect on NTS ability 42–45. How post-assessment debriefing affects the NTS of trainees in different ways and situations and whether NTS can be retained are aspects that need further exploration and discussion.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, 43% (n=23 of 54) of the included studies underwent post-assessment debriefing. Four studies using debriefing as a hypothesis supported its positive effect on NTS ability 42–45. How post-assessment debriefing affects the NTS of trainees in different ways and situations and whether NTS can be retained are aspects that need further exploration and discussion.…”
Section: Resultsmentioning
confidence: 97%
“…Four studies using debriefing as a hypothesis supported its positive effect on NTS ability. [42][43][44][45] How post-assessment debriefing affects the NTS of trainees in different ways and situations and whether NTS can be retained are aspects that need further exploration and discussion. The system was used to evaluate the performance.…”
Section: Training Of Raters and Feedback From Participantsmentioning
confidence: 99%
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The second focus of VS-integrated learning contexts in undergraduate medical education was emergency and pediatric emergency medicine training, with 14 articles ( 10 , 16 – 18 , 29 , 30 , 34 , 39 , 51 , 55 , 68 , 79 , 93 , 101 ) published recently. Among them, eight studies ( 10 , 16 – 18 , 30 , 34 , 39 , 68 ) used VS-based teaching in pediatric emergencies. The VS simulators used in these studies were mainly based on virtual patient cases, and simulated the clinical critical events.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, unstructured debriefing can be useful in revealing various details of a learners' experience [18]. An RCT comparing virtual environments with and without debriefing revealed that computer debriefing improved midwifery students' nontechnical skills, self-efficacy, and knowledge [76]. As a result, when using IVR simulation, time allocated is needed for debriefing so that students can share their insights and further develop their knowledge [48].…”
Section: Discussionmentioning
confidence: 99%